2022
DOI: 10.1021/acsami.1c24417
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Bridged Bonds Boost the Conversion Reaction of the Flexible Self-Supporting MnS@MXene@CNF Anode for High-Rate and Long-Life Lithium-Ion Batteries

Abstract: Manganese sulfide (MnS) has been found to be a suitable electrode material for lithium-ion batteries (LIBs) owing to its considerable theoretical capacity, high electrochemical activity, and low discharge voltage platform, while its poor electrical conductivity and severe pulverization caused by volume expansion of the material limit its practical application. To improve the rate performance and cycle stability of MnS in LIBs, the structure-control strategy has been used to design and fabricate new anode mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Electrospinning technology decentralizes MXene nanosheets, and endows multifunctional electrodes with a self-supporting ability. Research on the structure of MXene-based carbon nanobers has been limited to capacitors and Li + /Na + batteries, [33][34][35][36][37] whereas the fascinating properties of ion removal and antibacterial performance in aqueous solution have yet to be investigated. This work is interesting because it exemplies the rational design of multifunction CDI electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning technology decentralizes MXene nanosheets, and endows multifunctional electrodes with a self-supporting ability. Research on the structure of MXene-based carbon nanobers has been limited to capacitors and Li + /Na + batteries, [33][34][35][36][37] whereas the fascinating properties of ion removal and antibacterial performance in aqueous solution have yet to be investigated. This work is interesting because it exemplies the rational design of multifunction CDI electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Light-weight and small-sized lithium ion batteries (LIBs) are becoming increasingly important because of the extensive utilization of miniaturized electronic devices. , Unfortunately, nonelectrochemical active conductive agents and binders commonly used in traditional powder anodes resulted in decreased content of active materials and increased internal resistance and thus gone against the achievement of high-energy density LIBs. , Numerous studies have shown that additive-free self-supporting anodes can effectively avoid the use of conductive agents/binders and ensure good electronic conductivity, ionic diffusivity, and structural stability, which have the potential to meet the market demand of light-weight and small-sized LIBs. , …”
Section: Introductionmentioning
confidence: 99%
“…3,4 Numerous studies have shown that additive-free self-supporting anodes can effectively avoid the use of conductive agents/binders and ensure good electronic conductivity, ionic diffusivity, and structural stability, which have the potential to meet the market demand of light-weight and small-sized LIBs. 5,6 Among various anode materials, metallic Sn has drawn increasing attention on account of high theoretical capacity (994 mAh g −1 ), high safety, high abundance, and low redox potential. 7 Although Sn displays great potential as a selfsupporting anode material, its practical application is still facing the problems of inferior cycling stability as a result of extremely large volume expansion during electrochemical cycling.…”
Section: Introductionmentioning
confidence: 99%
“…[40,41] Particularly, the heteroatomdoped carbon materials can enlarge the interlayer distance, modify the electron structure of carbon materials, and facilitate the electron conduction in nanocomposite materials, increasing more active sites for Na + storage, thus achieving enhanced cyclic stability with a high energy or power density. [42][43][44] For example, Lee, [5] Gao [7] and Wu [8] et al synthesized the integrating metal sulfide into S-doped carbon materials to enhance the cycle stability and reversibility. It confirms that S-doped carbon could increase the electronic conductivity and kinetic reaction rate, buffer the huge volume expansion, and enhance the Na + storage capacity.…”
Section: Introductionmentioning
confidence: 99%
“…
electrochemical energy storage systems for replacement of LIBs worrying. [4][5][6] The emerging sodium-ion batteries (SIBs), whose metal sodium are earth-abundant, evenly distributed and low cost, still faced the issue of poor power density and relatively inferior cyclic stability similar to LIBs. [7][8][9][10][11][12][13] Sodium-ion hybrid capacitors (SIHCs) were emerged and introduced in 2012, containing a capacitor cathode and faradaic battery anode, and integrated the strengths of supercapacitors and batteries, thus exhibited high energy density without sacrificing the power density and large operating potential windows.
…”
mentioning
confidence: 99%